2017
DOI: 10.3390/polym9050183
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Polycaprolactone/Aloe Vera_Chitosan Nanofibrous Asymmetric Membranes Aimed for Wound Healing Applications

Abstract: Today, none of the wound dressings available on the market is fully capable of reproducing all the features of native skin. Herein, an asymmetric electrospun membrane was produced to mimic both layers of skin. It comprises a top dense layer (manufactured with polycaprolactone) that was designed to provide mechanical support to the wound and a bottom porous layer (composed of chitosan and Aloe Vera) aimed to improve the bactericidal activity of the membrane and ultimately the healing process. The results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 115 publications
(154 reference statements)
10
104
0
Order By: Relevance
“…It was reported that the hydrophilic scaffolds in the range of 40°–70° exhibited maximum fibroblast cell adhesion and proliferation. The contact angle of PU/olive/honey/propolis lies within these limits which might have favored the enhanced HDF adhesion and proliferation .…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the hydrophilic scaffolds in the range of 40°–70° exhibited maximum fibroblast cell adhesion and proliferation. The contact angle of PU/olive/honey/propolis lies within these limits which might have favored the enhanced HDF adhesion and proliferation .…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the use of bioactive materials together with PCL for the preparation of the electrospun mats has received great attention for novel development of membranes with superb cell proliferation and wound dressing [31][32][33][34]. For example, Correia and co-workers [35] investigated the use of extracted aloe vera chitosan nanofibrous materials and the subsequent fabrication using electrospinning method in the application of skin recovery and wound healing. It was discovered that the electrospun membranes promote the rapid cell proliferation and migration.…”
Section: Electrospun Nanoparticlesmentioning
confidence: 99%
“…It comprises a top dense layer (manufactured with polycaprolactone) that was designed to provide mechanical support to the wound and a bottom porous layer (composed of chitosan and AV) aimed to improve the bacterial activity of the membrane and ultimately the healing process. Miguel et al [36] obtained the results that the produced asymmetric membranes displayed porosity, wettability, as well as mechanical properties similar to those presented by the native skin.…”
Section: Aloe Vera Gel Scaffolds With Natural (Curcumin and Eggshell mentioning
confidence: 76%